APPLICATION OF PREMARITAL GUIDANCE THROUGH MIDODARENI TRADITION IN FORMING FAMILY HARMONY - Iswandari, Anisa; Rasmanah, Manah; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2024)
This study explores how applying premarital guidance through the midodrine tradition shapes family harmony. This research uses a qualitative methodology, namely the Field Research technique. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusions. The data sources in this study are primary and secondary, and the data obtained will be analyzed by description. Based on the study's results, it is known that applying premarital guidance through the Midodareni tradition makes the bride-to-be couple provisions as brides and can also know how to form a harmonious family. Premarital guidance through the midodrine tradition is carried out through five stages: Jonggolan, Catur Vedha, Tantingan, Wilujengan Majemukan, and Angsul-Angsul. So it can be concluded that the application of premarital guidance through the midodareni tradition in Forming Family Harmony is very successful, as seen from the decline in divorce rates in Nunggal Sari Village, Rimau Island District, Banyuasin Regency.